Internal governance mechanisms and audit fees : the moderating role of political connection and regulatory oversight / Norziaton Ismail Khan - Ismail Khan, Norziaton (2013)
This study has four (4) broad objectives. The first objective is to investigate whether politically connected (PCON) firms pay higher audit fees than non-PCON firms. The second objective is to examine the moderating effect of political connections (PCON versus non-PCON) on the association between the internal governance mechanisms, specifically, audit committee (AC) and internal audit functions (IAF), and audit fees. The third objective is to investigate whether high regulated firms (HRFs) pay higher audit fees than less regulated firms (LRFs). The fourth objective is to examine the moderating effect of regulatory oversight (HRF versus LRF) on the association between the above mentioned internal governance mechanisms and audit fees. This study is conducted in the Malaysian corporate setting that is unique due to the high involvement of the government in business (resulting in significantly high political connectedness with businesses) and the stringent regulatory oversight by the Central Bank of Malaysia (Bank Negara Malaysia) on financial institutions. In addition, the Bursa Malaysia revised its Listing Requirements to enhance the internal governance mechanisms in 2008, thus providing an opportunity to examine the audit fees issue from the demand side perspective both for the PCON firms and the HRFs. This research draws from three theories, namely, the agency theory, political embeddedness perspective and institutional theory, to form the framework and develop the hypotheses to be examined. Six (6) hypotheses are developed and tested, using data from 209 sample firms from years 2005 to 2009, that are before and after the revision of the Bursa Malaysia Listing Requirements in 2008 (BMLR 2008). The data were collected from the firms‟ annual reports and DataStream. In addition, interviews were conducted with selected external auditors, heads of the internal auditors and regulators that ascertain the existence of the demand side explanation for the audit fees. This study is important as it provides additional knowledge about the impact of the revised BMLR 2008 on AC characteristics and IAF attributes for PCON firms since most prior research was conducted before 2008. Specifically, it is evidenced that PCON firms have higher audit fees due to improved internal governance mechanisms which demand for increase in audit effort. Further, this study also provides support that HRFs firms have higher audit fees than LRFs due to the existence of an industry-specific regulator, over and above the capital market regulator, which requires more audit effort thus, increase in audit fees. As such, this study provides evidence and implications for regulators and others concerned with establishing guidelines and listing rules pertaining to internal governance mechanisms in an institutional context such as Malaysia.